The IMPLEMENTATION OF AUTONOMOUS WAYPOINT IN RECONNAISSANCE PLANE (UNMANNED AERIAL VEHICLE) UAV GALAK-24 USE WITH MISSION PLANNER - Huda, Muhamat Maariful; Herlambang, Luthfan; Kuncoro, Eko (Jurnal Telkommil, 2021)
Abstract: UAV or unmanned aerial vehicle is an air vehicle or what we often call an airplane that is controlled without a crew but controlled by a pilot remotely using a remote control. This study uses quantitative experiment methods because in this study it must be carried out when the UAV is flying using the autonomous waypoint method. Running the UAV with the autonomous waypoint method, we can use the Mission Planner software. First, we have to install the application on the mission planner and install pixhawk on the UAV which will act as the UAV brain that will receive and execute flight commands that will be sent by the mission planner later. The mission planner can also directly display flight data such as UAV altitude, UAV speed, UAV location, then the mission planner can also store flight data run by the UAV. The Autonomous waypoint method has been widely used in the military field, such as to carry out attacks on the enemy, reconnaissance, and patrol in an area quickly, and can also reduce casualties during combat operations.